Locally soluble AFA-groups - Dashkova, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Let $A$ be an $RG$-module, where $R$ is a ring, $G$ is a locally solvable group, $C_G (A) = 1$, and each proper subgroup $H$ of $G$ for which $A/C_A(H)$ is not an Artinian $R$-module is finitely generated. It is proved that a locally solvable group $G$ that satisfies these conditions is hyperabelian if R is a Dedekind ring. We describe the structure of $G$ in the case where $G$ is a finitely generated solvable group, $A/C_A(H)$ is not an Artinian $R$-module and $R$ is a Dedekind ring.